Memes as hate speech: Violence, humour and criticism around the image of Irene Montero - Martínez-Sanz, Raquel; Durántez-Stolle, Patricia; Simón-Astudillo, Iris (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research presents a content and cross-modal discourse analysis of memes (n=191) alluding to the Spanish Minister of Equality, Irene Montero, with special attention to the representation of violence. Hatred appears as a constant (90.8%) by ridiculing her personal life and criticising her political management, often through insults and comparisons. It is confirmed that misogynist hate has permeated the meme, proving its capacity to interfere in the public image of women, resorting to classic tropes and strategies, such as dehumanisation, exposure of private aspects or questioning physical appearance.